Diagnosing Students' Conception of Wave Propagation Using the Five-Tier Isomorphic Instrument - Riska Fitriani; Maison; Asrial; Sri Purwaningsih; Rita Asma (Jurnal Penelitian Pendidikan IPA, 2023)
This research aims to develop and apply a five-tier isomorphic instrument to determine the concept of wave propagation. The research design in this study is a mixed method research design in development and implementation instrument. Quantitative data was collected on 151 students in class XII MIPA SMA Negeri 1 Jambi City using an isomorphic instrument in the form of a five-tier diagnostic test. The test instrument was first tested for validity and reliability. The validity performed includes content and construct validity. Content validity is determined based on the % False Positive (FP) and False Negative (FN), which must be <10%. Construct validity is carried out by calculating factor analysis. Meanwhile, reliability is determined based on Cronbach's Alpha coefficient with r table = 0.413 (significance level 5%). The research results show that the instrument is very valid and reliable. The average understanding of students' concepts in wave propagation material is classified in the low category because the percentage obtained is <30%, namely 16% in all four tiers. Most students' conceptions are in the category of lack of knowledge regarding wave propagation, with a percentage of 23.5%.